An Analysis of the Effectiveness of Social Media as a Promotional Tool for Perlang Tourism Village - Devylia, Devylia (CV. Austronesia Akademika, 2025)
Rural tourism villages in Indonesia face increasing challenges in gaining visibility in the competitive digital tourism landscape, despite their rich cultural and natural assets. Perlang Tourism Village in Central Bangka Regency exemplifies this issue, as its promotional efforts via digital platforms remain fragmented and underdeveloped. This study investigates the effectiveness of social media as a promotional tool for Perlang, aiming to assess how visual storytelling, user-generated content (UGC), and platform-specific strategies influence destination branding and tourist engagement. Employing a qualitative case study approach, the research utilizes secondary data including social media metrics, tourism reports, and literature on digital promotion. The analysis reveals that while Instagram, YouTube, and TikTok present unique opportunities, their current usage by Perlang lacks coherence, regularity, and platform optimization. Instagram posts are sporadic and visually inconsistent, YouTube is inactive, and TikTok lacks an official presence despite growing organic content under the #Perlang tag. Moreover, the absence of influencer partnerships and structured UGC campaigns undermines Perlang’s potential to build trust and emotional connections with prospective tourists. The findings emphasize that effective rural tourism promotion requires a participatory and strategic digital approach incorporating targeted content, demographic segmentation, and emotionally resonant narratives. In conclusion, this research highlights the transformative potential of integrated social media strategies in enhancing the digital visibility of rural tourism destinations and recommends the adoption of community-driven storytelling and influencer collaborations to establish a compelling and competitive online identity for Perlang Village.